Stress Controlled Shape Optimization of 2D Elastic Structures - Gutkowski, W.; Zawidzka, J.; Zawidzki, J. (Engineering Transactions, 2004)
A simple and effective method of stress-controlled shape optimization of 2D linear elastic structures is presented. The main elements of the method are: adaptive FE grids fitting well to the structure shape at each iteration step of the proposed simple optimization algorithm and the concept of stress level factor, controlling directly the design variables being the grid parameters. Several examples of beam-type and plate-type 2D structures are investigated. A few iterations only are needed in order to reach a nearly optimal solution.